ARCTIC: durvalumab with or without tremelimumab as third-line or later treatment of metastatic non-small-cell lung cancer - D. Planchard; N. Reinmuth; S. Orlov; J. R. Fischer; S. Sugawara; S. Mandziuk; D. Marquez-Medina; S. Novello; Y. Takeda; R. Soo; K. Park; M. McCleod; et al. (Annals of Oncology, 2020)
Background: Many patients with metastatic non-small-cell lung cancer (mNSCLC) experience disease progression after first- and second-line treatment; more treatment options are required for these patients. ARCTIC, a phase III, randomized, open-label study, assessed durvalumab ± tremelimumab versus standard of care (SoC) as ≥ third-line treatment of mNSCLC. Patients and methods: ARCTIC comprised two independent sub-studies. Study A: 126 patients with ≥25% of tumor cells (TCs) expressing programmed cell death ligand-1 (PD-L1) were randomized (1 : 1) to durvalumab [up to 12 months 10 mg/kg every 2 weeks (q2w)] or SoC. Study B: 469 patients with PD-L1 TC <25% were randomized (3 : 2 : 2 : 1) to durvalumab + tremelimumab (12 weeks durvalumab 20 mg/kg + tremelimumab 1 mg/kg q4w then 34 weeks durvalumab 10 mg/kg q2w), SoC, durvalumab (up to 12 months 10 mg/kg q2w), or tremelimumab (24 weeks 10 mg/kg q4w then 24 weeks q12w). Primary end points: overall survival (OS) and progression-free survival (PFS) for durvalumab versus SoC (study A; descriptive only) and durvalumab + tremelimumab versus SoC (study B). Results: Study A: median OS 11.7 (durvalumab) versus 6.8 (SoC) months {hazard ratio (HR) 0.63 [95% confidence interval (CI), 0.42–0.93]}; median PFS 3.8 (durvalumab) versus 2.2 (SoC) months [HR 0.71 (95% CI, 0.49–1.04)]. Study B: median OS 11.5 (durvalumab + tremelimumab) versus 8.7 (SoC) months [HR 0.80 (95% CI, 0.61–1.05); P = 0.109]. Median PFS of 3.5 months for both groups [HR 0.77 (95% CI, 0.59–1.01); P = 0.056]. Treatment-related grade 3/4 adverse events: 9.7% (durvalumab) and 44.4% (SoC; study A) and 22.0% (durvalumab + tremelimumab) and 36.4% (SoC; study B). Conclusions: In heavily pretreated patients with mNSCLC, durvalumab demonstrated clinically meaningful improvements in OS and PFS versus SoC (patients with PD-L1 TC ≥25%); numerical improvements in OS and PFS for durvalumab + tremelimumab versus SoC were observed (patients with PD-L1 TC <25%). Safety profiles were consistent with previous studies. Trial ...